2019
DOI: 10.47941/jbsm.279
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF STUDENT RETENTION STRATEGIES ON PERFORMANCE OF TVETs IN NAIROBI COUNTY, KENYA

Abstract: Purpose: The study sought to evaluate the power of student retention strategies on performance of TVET institutes in Kenya: a case study of Nairobi City County. In order to capture the required information, the study is guided by four objectives; to assess the influence of student orientation and induction strategy, student support programs strategy, customer relation management, and student involvement and participation on performance of TVET institutes in Kenya. This study is anchored on drive reduction theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Findings from the study found that the major factors negatively affecting student success or programme completion rates include individual and social factors, institutional policies, structures and systems, and friendliness of instructors and peers at the institutions. Magut & Kihara (2019) found that student induction strategy, which comprised introduction to the institution's culture, provision of learning course materials and outline of expectations from students, influenced student success.…”
Section: Factors Influencing Students' Success In Tvet Collegesmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from the study found that the major factors negatively affecting student success or programme completion rates include individual and social factors, institutional policies, structures and systems, and friendliness of instructors and peers at the institutions. Magut & Kihara (2019) found that student induction strategy, which comprised introduction to the institution's culture, provision of learning course materials and outline of expectations from students, influenced student success.…”
Section: Factors Influencing Students' Success In Tvet Collegesmentioning
confidence: 99%
“…Source: Authors' compilation using numerous selected past studies Studies that were reviewed and used in developing the theoretical framework of factors influencing students' access to TVET colleges include Kilpatrick & Allen (2001), Hoeckel, K. (2008), Biyo-Yara (2008), Simiyu (2009), Khaguya (2014), Ayiah-Mensah, Mettle & Coker-Ayimah (2014), Ayonmike (2014), NSW Department of Industry (2016), Gewer (2016), Blom (2016), Alishiri & Saadatmand (2016), Stratton et al (2017, Nzembe (2018), Safarmamad (2019), Kiplangat (2020), Wasike & Maiyo (2020), Omar et al (2020), Langat, Ngeno, Omboto & Ambuli (2021a), Ambuli (2021b), andZhi &Atan (2021). Concurrently, studies which examined factors influencing student success in TVET colleges include Hoeckel (2008), Fieger (2015a), Fieger (2015b, Kiplagat (2016), National Centre for Vocational Education Research (2017), Badenhorst & Radile (2018), Henriques (2018, Nzembe (2018), Gaffoor & van der Bijl (2019) and Magut & Kihara (2019). Kilpatrick & Allen (2001) analysed factors influencing demand for vocational education and training (VET) courses by school students and their families.…”
Section: Figure 1: Theoretical Frameworkmentioning
confidence: 99%
“…Therefore, it is important to concede that the integration process could be hampered by the individual student's attributes and the factors found within the institution. TVET Colleges invest substantially in resources, but in some instances, enrolled students leave the institution before completing their courses (Magut & Kihara, 2019). This student dropout trend can be attributed to the institution's lack of adequate awareness of student integration factors.…”
Section: Student Integration and Persistencementioning
confidence: 99%
“…Institutions can use surveys to ascertain factors that promote student attrition. The survey findings could assist in enhancing the students' integration process (Magut & Kihara, 2019). Student support programs critical to student integration include induction, educational advising, academic resources, study skills, cultural activities, and social adjustment.…”
Section: Student Integration and Persistencementioning
confidence: 99%
“…Workforce diversity makes every single person feel more valued thereby making them give the best in their duties. [9] noted that St. Paul's University and The Presbyterian University of East Africa have engaged in a number of activities to manage the diversity of their workforce. Moreover, they provide training and education on workforce diversity that targets sexual harassment, value variations (e.g.…”
Section: Introductionmentioning
confidence: 99%